A robust method for mechanical characterization of heterogeneous materials by nanoindentation grid analysis. (September 2020) - Sanchez-Camargo, Cesar-Moises; Hor, Anis; Salem, Mehdi; Mabru, Catherine
Abstract: The study presents the analysis of the contour plots obtained from nanoindentation grids conducted on CuZn40Pb2 brass and W-Cu, which are heterogeneous materials having different microstructure and mechanical properties. The aim is to increase the detection capacity of the mechanical properties of the phases respect to the statistical analysis, but also to propose a formulation for the inverse analysis of nanoindentation data allowing the full elastoplastic characterization. Analysis of contour plots provides curves where the mean value of the phases and the bulk value can be read directly. In complex microstructures, this gives access to the predominant mechanical properties facilitating the interpretation of the results. The estimation of the phase fractions by this proposed method is better than the estimation performed with statistical analysis. The estimation of the standard deviation is equivalent to the statistical analysis in most cases; however the difference is large on skewed distributions. The formulation of the objective function for inverse analysis is able to manage large number of indentations, producing elastoplastic parameters with excellent accuracy compared to parameters identified by tensile test. Graphical abstract: Unlabelled Image Highlights: Analysis of the nanoindentation data gathered by a grid applied on the surface of the investigated heterogeneous materials Detection of phases and estimation of their mechanical properties Phase fraction detection and estimation by different methods Elastoplastic characterization of the phases and the bulk material by inverse analysis coupled with finite element modeling Improved results against the statistical analysis using deconvolution technique